Antibiotic Resistance Level in Bacterial Isolates from the Kakuri Industrial Drain In Kaduna, Nigeria. - A A, Haroun; Y, Magaji; S, Denwe; M D, Muktar; K k, Kamaluddeen (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2017)
Bacterial isolates from the Kakuri drain in Makera District of Kaduna town were subjected to antibiotic resistance test using the Kirby-Bauer Disc-diffusion method. A total of thirty three (33) strains isolated from the drain were tested for their antibiotic resistance capacity using the M13, M14 and M51 Mastring Discs. The result obtained, indicated that the strains of Bacteria isolated from the drain are resistant to most of the tested antibiotics. Data obtained showed that all the isolates had multiple antibiotic resistance (MAR). All the strains showed resistance to Chloramphenicol (100%) at 25ug; Erythromycin(100%) at 5ug ; Tetracycline(100%) at25ug; Cotrimixazole (100%) at 25ug; Sulphatriad (80%) at 200ug Augmentin((100%) at 10ug ; Ampicillin (100%) at 10ug; among others, but were found to be sensitive to Streptomycin(40%) at 10ug on M13; sensitive to a lesser extent to Colostram sulphate(40%) at 25ug and Gentamicin(40%) at 10ug on M14. While on M51, disk , Strains were only noted to be sensitive to Gentamicin.